2005
DOI: 10.1111/j.1439-0507.2005.01097.x
|View full text |Cite
|
Sign up to set email alerts
|

Scutular tinea of the scrotum: report of two cases

Abstract: Infections caused by dermathophytes in the scrotal skin are uncommon especially due to Microsporum gypseum, which may form scutular or favus-like lesions. We report two patients with this type of tinea: one immune suppressed by HIV infection and another immunocompetent without comorbidity. In the literature we found only two reports in immunocompetent patients and some in immune suppressed with similar symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…Finally, M. gypseum was isolated from culture of progressed lesions. To our knowledge, this geophilic dermatophyte has been reported in only a few cases of HIV patients so far, and always in resource-poor settings [5, 6, 7, 8]. Our case, therefore, is the first case of diffuse tinea incognito due to M. gypseum reported in Western countries in a patient with prolonged professional exposure to soil and dust and severe immune suppression [9].…”
Section: Discussionmentioning
confidence: 78%
“…Finally, M. gypseum was isolated from culture of progressed lesions. To our knowledge, this geophilic dermatophyte has been reported in only a few cases of HIV patients so far, and always in resource-poor settings [5, 6, 7, 8]. Our case, therefore, is the first case of diffuse tinea incognito due to M. gypseum reported in Western countries in a patient with prolonged professional exposure to soil and dust and severe immune suppression [9].…”
Section: Discussionmentioning
confidence: 78%
“…For example, Lu et al reported six cases, five of which were caused by N. gypsea . Sporadic cases from Japan and Brazil also showed that N. gypsea was the prevalent agent …”
Section: Discussionmentioning
confidence: 98%
“…Favus of the scalp is typically a childhood disease, yet adult favus‐like scrotal tinea are uncommon. However, tinea of scrotum because of N. gypsea presenting as favus‐like lesions in immunocompromised or immunocompetent patients are reported more and more in China and Brazil . This is the first report of dramatic morphology in vivo of scrotum N. gypsea infection demonstrated by SEM and TEM.…”
mentioning
confidence: 77%
“…Although dermatophytes may colonize the scrotum, they typically do not infect scrotal skin. However, tinea of scrotum is reported rarely as a specific type of Microsporum gypseum infection, presenting as white‐paint‐dot appearance scutular‐like or pseudomembranous‐like lesions in immunocompromised or immunocompetent patients . According to the most recent taxonomy, M. gypseum is now called Nannizzia gypsea .…”
mentioning
confidence: 99%